BCT454-2: Building construction technology / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2019)
The general aim of the course is to provide a basic knowledge and understanding on the different types of superstructure framing system for building. The course also covers a continuous understanding on types and methods of construction of building elements and finishes as well as theoretical study on related external and civil works involve in building construction.